2007
DOI: 10.1007/s10298-007-0252-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of medicinal plants in the treatment of diabetes in Morocco

Abstract: Le traitement actuel du diabète est efficace dans la baisse de la glycémie, cependant le contrôle adéquat quotidien de la glycémie est très difficile à atteindre dans la plupart des cas, ce qui conduit à long terme à l'émergence de complications très sérieuses. L'essor récent de la phytothérapie offre une opportunité pour trouver des molécules naturelles susceptibles d'exercer des effets bénéfiques sur la régulation du métabolisme glucidique en évitant les effets secondaires des substances synthéti-ques. Le Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
2
21
0
2
Order By: Relevance
“…Healing plants remain the only way of treatment for 70 % of the world population (Rejdali, 1996, Peyron, 2000 and for 80 % of the African population (OMS, 2003). The percentage of use of healing plants in the preventive and curative virtues varies in the studied regions, from 50 to 80 % (Eddouks et al, 2007). More than 25000 plants are used in the pharmacopoeia and more than 50 % of pharmaceutical products available on the market are of natural origin Journal of Applied Biosciences 84:7707 -7722 ISSN 1997-5902 (Hamilton, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Healing plants remain the only way of treatment for 70 % of the world population (Rejdali, 1996, Peyron, 2000 and for 80 % of the African population (OMS, 2003). The percentage of use of healing plants in the preventive and curative virtues varies in the studied regions, from 50 to 80 % (Eddouks et al, 2007). More than 25000 plants are used in the pharmacopoeia and more than 50 % of pharmaceutical products available on the market are of natural origin Journal of Applied Biosciences 84:7707 -7722 ISSN 1997-5902 (Hamilton, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, several medicinal plants are used for the treatment of diabetes mellitus [2] . Ethnobotanic inquiries have recorded the plants used in such a perspective, among which Citrullus colocynthis (C. colocynthis) represent one of the most commonly used species [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, many authors have shown that the percentage of the use of medicinal plants varies between 52 and 90%, depending on the region or where the investigation has been undertaken (Sekkat, 1987;Magoua, 1991;Nabih, 1992;Bellakhdar, 1997;Ziyyat et al, 1997;Eddouks et al, 2007;Benkhnigue et al, 2011). This strong use of medicinal plants is due to the strong belief of diabetic patients in their efficiency (95.86%), accessibility (2.86%) as well as their low cost (1.29%).…”
Section: Characteristics Of the Diabetic Population According To Theimentioning
confidence: 99%
“…In addition to these factors, the contribution of religion in the field of medicinal plants among the plants cited asanti-hyperglycaemic, some are drawn directly from the Koran and religious manuscripts. This is particularly the case of Lawsonia inermis, Trigonella foenum-graecum, Ziziphus lotus, Punica granatum, Myrtus communis, Nigella sativa, Allium sativum, Allium cepa, Olea europaea, Ficus garcia, and Zingiber officinalis (Eddouks et al, 2007).…”
Section: Characteristics Of the Diabetic Population According To Theimentioning
confidence: 99%